Java 7 recipes a problem-solution approach - Juneau, Josh (Berkeley, California Apress, 2011)
Java 7 Recipes offers solutions to common programming problems encountered every day while developing Java-based applications. Fully updated with the newest features and techniques available, Java 7 Recipes provides code examples involving Servlets, Java FX 2.0, XML, Java Swing, and much more. Content is presented in the popular problem-solution format: Look up the programming problem that you want to solve. Read the solution. Apply the solution directly in your own code. Problem solved! The problem-solution approach sets Java 7 Recipes apart from other books on the topic. Java 7 Recipes is focused less on the language itself and more on what you can do with it that is useful. The book respects your time by always focusing on a task that you might want to perform using the language. Solutions come first. Explanations come later. You are free to crib from the book and apply the code examples directly to your own projects. Covers all-new release of Java: Java 7. Focuses especially on up-and-coming technologies such as Java FX 2.0. Respects your time by focusing on practical solutions you can implement in your own code.
Electronic reproduction.
Keywords: Java (Computer program language); Application software -- Development; Object-oriented programming (Computer science) .